رؤية طه جابر العلواني في إسلامية المعرفة وسبل تحقيقها: Taha Jabir Al-Alwani's Vision for the Islamization of Knowledge and Ways to Achieve it - Najeeb, Hameedullah; Mohammad Osmani, Noor (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يهدف هذا البحث إلى استكشاف رؤية طه جابر العلواني لمفهوم "إسلامية المعرفة"، ويستعرض أهمية تحقيقها في الواقع المعاصر. يركز العلواني على الحاجة إلى دمج القيم الإسلامية في مناهج التعليم والمعرفة العلمية، مؤكداً على ضرورة إعادة بناء الفكر الإسلامي بطريقة تُعيد له دوره الريادي في تشكيل الحضارة الإنسانية. وسلك البحث المنهج الاستقرائي والتحليلي ليتوافق مع طبيعة هذا الموضوع. ومن أبرز نتائجه: تحديد مفهوم إسلامية المعرفة بأنها عملية تكامل بين العلوم الإسلامية والمعارف الحديثة، وضرورة توسيعها في مجالات متعددة، مثل إصلاح المجتمع، وقيم الأخلاق، والتعليم والتربية، والسياسة، وليس حصرها فقط في المجال الديني، بهدف تحقيق شمولية معرفية. ABSTRACT The research aims at exploring Taha Jabir Al-‘Alwani's perspective on the concept of "Islamization of Knowledge," examining its different aspects and the importance of implementing it in contemporary reality. Al-‘Alwani emphasizes the need to integrate Islamic values into educational curricula and scientific knowledge, asserting the necessity of reconstructing Islamic thought to restore its pioneering role in shaping human civilization. The study employed an inductive and analytical approach suited to the nature of this topic. The study discovered that the "Islamization of Knowledge" to him is a process of integration between Islamic sciences and modern knowledge, and the need to expand it into various fields, such as social reform, ethics, education and pedagogy, and politics, rather than confining it solely to the religious domain, in order to achieve comprehensive knowledge.